2022
DOI: 10.3310/nihropenres.13290.2
|View full text |Cite
|
Sign up to set email alerts
|

Remote care in UK general practice: baseline data on 11 case studies

Abstract: Background: Accessing and receiving care remotely (by telephone, video or online) became the default option during the coronavirus disease 2019 (COVID-19) pandemic, but in-person care has unique benefits in some circumstances. We are studying UK general practices as they try to balance remote and in-person care, with recurrent waves of COVID-19 and various post-pandemic backlogs. Methods: Mixed-methods (mostly qualitative) case study across 11 general practices. Researchers-in-residence have built relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Our ongoing ethnographic research in 11 general practices across the UK 5 suggests that achieving continuity, especially for the most disadvantaged and vulnerable, takes additional resource and creative action from both clinicians and support staff (Ladds E, Greenhalgh T, unpublished data, 2023). It may be tempting to conclude that general practice has become so complex and is under so much pressure that continuity has simply become too difficult to achieve.…”
Section: Continuity Is Keymentioning
confidence: 99%
See 2 more Smart Citations
“…Our ongoing ethnographic research in 11 general practices across the UK 5 suggests that achieving continuity, especially for the most disadvantaged and vulnerable, takes additional resource and creative action from both clinicians and support staff (Ladds E, Greenhalgh T, unpublished data, 2023). It may be tempting to conclude that general practice has become so complex and is under so much pressure that continuity has simply become too difficult to achieve.…”
Section: Continuity Is Keymentioning
confidence: 99%
“… 3 Multiple system-level pressures — including rising workload, under-resourcing and staffing, increased policy emphasis on rapid access and plurality of provision, and societal fragmentation resulting in high turnover of patients and staff (especially in deprived localities) — have contributed to a de-prioritisation of continuity within UK general practice. The emergence of multidisciplinary teams covering a wide range of roles 4 and the introduction and expansion of digital and remote modalities 5 have created both challenges and opportunities for the delivery of continuity. 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sub-study reported here emerged from the ongoing Remote by Default 2 (RBD2) study whose protocol 5 and baseline findings 6 have been published. RBD2 has three main work packages.…”
Section: Origin Of This Sub-studymentioning
confidence: 99%
“…Previous empirical work by the study team found that people in supporting roles had to extend that support to help patients navigate online access to healthcare ( Greenhalgh et al , 2022b ). Digital disparities, such as ownership of digital devices and access to the internet, were exacerbated by other difficulties in accessing remote care ( Rosen et al , 2022 ).…”
Section: Introductionmentioning
confidence: 99%